Extraction of a metallic susceptor after accidental ingestion of the heated tobaccostick TEREA™: a case report - Koki Higashi; Yuhki Koike; Yuki Sato; Shinji Yamashita; Yuka Nagano; Tadanobu Shimura; Takahito Kitajima; Kohei Matsushita; Kazuki Yokota; Keishiro Amano; Yoshinaga Okugawa; Yuji Toiyama (BMC, 2023)
Abstract Background Tobacco ingestion is widely known to cause nicotine toxicity, which may result in severe symptoms. Two heated tobacco sticks, called TEREA™ and SENTIA™, were launched in 2021 by Philip Morris International (New York, NY, USA), and their ingestion is associated with a risk of bowel injury because they contain a partially pointed metallic susceptor. However, this risk is not well known to the general public or healthcare providers. To increase awareness of this risk, we herein report a case involving extraction of a metallic susceptor after ingestion of the heated tobacco stick TEREA™. Case presentation A 7-month-old girl presented to the emergency department of a nearby hospital because she was suspected to have accidentally swallowed heated tobacco. Although she presented with no symptoms related to nicotine poisoning, abdominal X-ray examination revealed a metal object in her stomach. According to a statement released by the Japan Poison Information Center, the TEREA™ heated tobacco stick contains a metallic susceptor with a rectangular shape and sharp corners. The patient was transferred to our department because of the risk of bowel injury, and upper gastrointestinal endoscopy was performed. No cigarettes were found by endoscopic observation; however, a metallic susceptor was located in the second part of the duodenum. We grasped it with biopsy forceps and carefully removed it using an endoscope with a cap attached to the tip. The post-endoscopic course was uneventful. Conclusions Some patients who ingest heated tobacco sticks might be exposed not only to the effects of nicotine but also to physical damage caused by a metallic susceptor. Infants and toddlers especially could swallow these sticks, therefore tobacco companies need to make the problem more public. Clinicians also should alert the problem, and pay attention to this risk in the clinical setting.